2013
DOI: 10.5187/jast.2013.55.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Characteristics and Profitability Analysis Based on Slaughter Age of Hanwoo Steers

Abstract: This study analyzed optimal slaughter ages and carcass traits to investigate factors that affect farm incomes. Carcass characteristics and economical analysis of 81 Hanwoo steers previously tested (Expt. 1) and 5,826 steers from Gangwon-Do, area A (Expt. 2) were used. In Expt. 1, the strongest relationship was between the slaughter age and the carcass weight based on the R 2 value, and the weakest relationship was between the slaughter age and the marbling score based on the R 2 . The slaughter age, marbling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Market weight correlation among the ten primal cuts was observed highest in the ribs at 0.84 followed by sirloin and top round at 0.77, shoulder at 0.75, strip loin and bottom round at 0.72, brisket at 0.70, tenderloin and chuck at 0.67, and the lowest in shank at 0.55 (p < 0.001). The correlation of CCW among the ten primal cuts was observed highest in the ribs and sirloin (0.89 and 0.81) followed by top round, shoulder, and strip loin (0.78, 0.77, 0.75) which is consistent with previous reports [5,24]. The BFT did not show a significant correlation with tenderloin, chuck, and shoulder, and showed a low significant positive correlation to the other seven primal cuts (0.11 to 0.42).…”
Section: Correlation Of Carcass Yield Traits With Primal Cuts Yieldsupporting
confidence: 92%
See 1 more Smart Citation
“…Market weight correlation among the ten primal cuts was observed highest in the ribs at 0.84 followed by sirloin and top round at 0.77, shoulder at 0.75, strip loin and bottom round at 0.72, brisket at 0.70, tenderloin and chuck at 0.67, and the lowest in shank at 0.55 (p < 0.001). The correlation of CCW among the ten primal cuts was observed highest in the ribs and sirloin (0.89 and 0.81) followed by top round, shoulder, and strip loin (0.78, 0.77, 0.75) which is consistent with previous reports [5,24]. The BFT did not show a significant correlation with tenderloin, chuck, and shoulder, and showed a low significant positive correlation to the other seven primal cuts (0.11 to 0.42).…”
Section: Correlation Of Carcass Yield Traits With Primal Cuts Yieldsupporting
confidence: 92%
“…Yield index:(11.06398 -[1.25149 × Backfat thickness (mm)] + [0.28293 × Ribeye area (cm 2 ) + [0.54768 × Carcass cold weight (kg)]) ÷ (Carcass cold weight (kg) × 100).2)Marbling score: 1-trace, 9-very abundant.a-c Means within the same row with different superscript are statistically different (p < 0.05). CCW, carcass cold weight; REA, ribeye area; BFT, backfat thickness; DP, dressing percentage; MS, marbling score; PCY, primal cuts yield https://doi.org/10.5187/jast.2021.e136of slaughter age while the MS of the Korean beef cattle regardless of sex increased 4.9 to 5.7 at 26 to 35 months of slaughter age[24]. Summing up, the carcass yield traits of Hanwoo beef such as market weight, CCW, REA, BFT, overall and individual prime cut yield, fat weight, and bone weight progressed until at the age of 27 to 28 months.…”
mentioning
confidence: 99%
“…The MS standard ranges from 1 to 9 in Korea [ 59 ]. The MS of Korean cattle steers (81 animals) raised at the Livestock Improvement Main Center of the National Agricultural Cooperative Federation in Korea increased from 6.0 to 7.06 as slaughter age increased from 26 to 31 months [ 68 ]. The highest profit in this steer group was for a slaughter age of 31 months.…”
Section: Management Factorsmentioning
confidence: 99%
“…The highest profit in this steer group was for a slaughter age of 31 months. In the same report [ 68 ], the MS in 5,826 Korean cattle steers from several farms in Gangwon Province was analyzed in 2010 to 2012; MS increased from 4.9 to 5.7 as slaughter age increased from 26 to 35 months. In this case, the optimum slaughter age for the highest profit was 28 months.…”
Section: Management Factorsmentioning
confidence: 99%
“…(2018) revealed that the IMF content rapidly enhanced between 12 and 28 months old, especially from 24 to 28 months old. Lee et al. (2013) observed that the profit of fattening Hanwoo steers was highest when the animals were slaughtered at 28 months of age, after that the profit decreased.…”
Section: Management Factorsmentioning
confidence: 98%